Mesoscale mixing of the Denmark Strait Overflow in the Irminger Basin - Koszalka, Inga Monika; Haine, Thomas W.N.; Magaldi, Marcello G. (Ocean Modelling, 2017)
Highlights: • Water mass transformation in Denmark Strait Overflow is localized in space/time • High transformation co-locates with maxima in eddy velocity variance and shear • Overflow eddies modulate the transformation, eddy heat flux divergence and shear Abstract: The Denmark Strait Overflow (DSO) is a major export route for dense waters from the Nordic Seas forming the lower limb of the Atlantic Meridional Overturning Circulation, an important element of the climate system. Mixing processes along the DSO pathway influence its volume transport and properties contributing to the variability of the deep overturning circulation. They are poorly sampled by observations however which hinders development of a proper DSO representation in global circulation models. We employ a high resolution regional ocean model of the Irminger Basin to quantify impact of the mesoscale flows on DSO mixing focusing on geographical localization and local time–modulation of water property changes. The model reproduces the observed bulk warming of the DSO plume 100–200 km downstream of the Denmark Strait sill. It also reveals that mesoscale variability of the overflow (‘DSO-eddies’, of 20-30 km extent and a time scale of 2–5 day) modulates water property changes and turbulent mixing, diagnosed with the vertical shear of horizontal velocity and the eddy heat flux divergence. The space–time localization of the DSO mixing and warming and the role of coherent mesoscale structures should be explored by turbulence measurements and factored into the coarse circulation models.